Hotel and resort management - Cobb, Victor (Wilmington, De Kaufman Press, 2023)
"Hotel And Resort Management | Hardcover is a comprehensive guide covering fundamental and advanced concepts in its field. This book is ideal for both beginners and experienced learners seeking in-depth knowledge."--
Preface -- Hotel management -- Hotel organization management -- The structure of hotel industry -- Customer management in hotel -- Service quality measurement in hotel industry -- Hotel staff management -- Hotel and motel industry -- Resort development -- Resort destination -- Seaside resort -- Bibliography -- Index
Reprint. Originally published in 2022.
Includes bibliographical references and index.
Keywords: Hospitality industry -- Management; Hotels -- Management; Resorts -- Management